Wave effects on buoyant plumes - Le, Huu Ti; Shuto, Nobuo; Arbhabhirama Anat; Ackermann, Norbert L.; Canadian Province of British Columbia (Bangkok : Asian Institute of Technology, 1973)
The effect of waves on buoyant plumes was studied in this paper, based on previous investigations into buoyant plumes in still ambient fluids or in cross streams. The waves generated in the experiments were restricted to long waves of small amplitudes only, in order to eliminate the effects of finite amplitudes and vertical velocities which may strongly affect the change of the plumes. On the other hand, the uniform distribution of the horizontal velocity makes the analysis easier, because the analogy to the plume in a uniform cross stream can be easily applied. From the observations, we can divide the trajectories of the plumes into three cases: - nearly vertical plume for high k - intermediate case - nearly horizontal plume for low k where k = Wo _U Wo : the average velocity of the waves taken over a half wave period. This distinction also depends on the ratio h/Do where h : the water depth in the flume Do : the diameter of the orifice Using the integral technique of the analysis, and assuming similarity, we can predict the plume changes with time. From this numerical method, we can only obtain the dilution rate for the first and third cases. In this study, two numerical solutions were obtained for the first case with k = 20.5 and h/D = 33.3 and for the third case with k = 3.54 and 0 h/D = 25. 0 We know that it is not feasible to measure the vertical velocity distributions as well as the concentration distributions along the plume. So the measurements of concentration was only carried out at the surface of the water just above the orifice. The experimental data were obtained for the dilution rate at the water surface just above the orifice only from 7 sets of h/Do , in which we have 3 values of D , 0.5, 0.75, and l.p cm, at almost 2 different densities of the ambient water whose Froude number ranged from 1 to 7, and the ratio k varying from 3 to 30. The experimental data are analyzed to give a semi-empirical formula combined theoretical consideration, and it is found that the formula can be applied with sufficient accuracy to the experimental range covered by the present analysis
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand .
Thesis (M.Eng.) - Asian Institute of Technology, 1973
Keywords: Wave mechanics; Ocean waves